Virial Black Hole Masses for Active Galactic Nuclei behind the Magellanic Clouds - Swayamtrupta Panda; Szymon Kozłowski; Mariusz Gromadzki; Marcin Wrona; Patryk Iwanek; Andrzej Udalski; Michał K. Szymański; Igor Soszyński; Paweł Pietrukowicz; Krzysztof Ulaczyk; Jan Skowron; Radosław Poleski; et al. (The Astrophysical Journal Supplement Series, 2024)
We use the spectroscopic data collected by the Magellanic Quasars Survey (MQS) and the photometric V - and I -band data from the Optical Gravitational Lensing Experiment (OGLE) to measure the physical parameters for active galactic nuclei (AGNs) located behind the Magellanic Clouds. The flux-uncalibrated MQS spectra were obtained with the 4 m Anglo-Australian Telescope and the AAOmega spectroscope ( R = 1300) in a typical ∼1.5 hr visit. They span a spectral range of 3700–8500 Å and have signal-to-noise ratios in a range of 3–300. We report the discovery and observational properties of 161 AGNs in this footprint, which expands the total number of spectroscopically confirmed AGNs by MQS to 919. After the conversion of the OGLE mean magnitudes to the monochromatic luminosities at 5100, 3000, and 1350 Å, we were able to reliably measure the black hole masses for 165 out of 919 AGNs. The remaining physical parameters we provide are the bolometric luminosities and the Eddington ratios. A fraction of these AGNs have been observed by the OGLE survey since 1997 (all of them since 2001), enabling studies of correlations between the variability and physical parameters of these AGNs.